Intrinsic decoherence mechanisms in the microcavity polariton condensate - EASTHAM, PAUL (American Physical Society, 2008)
The fundamental mechanisms which control the phase coherence of the polariton Bose-Einstein condensate (BEC) are determined. It is shown that the combination of number fluctuations and interactions leads to decoherence with a characteristic Gaussian decay of the first-order correlation function. This line shape, and the long decay times ( 150 ps) of both first- and second-order correlation functions, are explained quantitatively by a quantum-optical model which takes into account interactions, fluctuations, and gain and loss in the system. Interaction limited coherence times of this type have been predicted for atomic BECs, but are yet to be observed experimentally.
PUBLISHED
Keywords: Condensed matter physics; Bose-Einstein condensate (BEC)